Structural, Optical, Photocatalytic and Antibacterial Properties of Hydrothermally Synthesised CuO–WO3 Heterojunction Nanocomposite - Jakkula, Rajendra Prasad; Suresh, Domala; Konda, Srinivasa Rao; Raghavapuram, Ramyashree (Asian Journal of Chemistry, 2026)
Nanostructured pure CuO and CuO-WO3 heterojunction composites were synthesised using a hydrothermal technique. The materials were analysed by XRD, SEM, TEM, AFM, EDX and FTIR to determine their physico-chemical properties. Monoclinic crystal structure and heterojunction composite that developed between the synthesised CuO and WO3 are indicated. The photocatalytic activity was investigated via the degradation of methylene blue under visible light, where the CuO–WO3 nanocomposite exhibited higher photocatalytic activity compared to the unmodified nanostructured CuO. The enhanced photocatalytic activity of the composite material is attributed to the suppressed recombination of photogenerated electron–hole pairs under visible-light irradiation and the increased generation of reactive oxygen species (ROS) facilitated by the presence of WO3. The antibacterial performance of the prepared materials was evaluated against Gram-positive and Gram-negative bacteria. In comparison to unmodified CuO, the CuO–WO3 nanocomposite demonstrated superior antibacterial activity due to better surface deposition and ROS-mediated bacterial cell membrane destruction, which was attributed to the interaction of the generated ROS with the cell membranes of bacteria. The enhanced performance is attributed to improved interfacial charge transfer, heterojunction-induced carrier separation and increased surface-active sites. The CuO–WO3 system demonstrates the significance of interfacial engineering and phase coupling in tailoring functional properties. These findings highlight the potential of such oxide-based composites as multifunctional agents for advanced environmental and antimicrobial applications.